2012
DOI: 10.1002/hyp.9240
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogeomorphic influences on alluvial gully erosion along the Mitchell River fluvial megafan

Abstract: Hydrogeomorphic processes influencing alluvial gully erosion were evaluated at multiple spatial and temporal scales across the Mitchell River fluvial megafan in tropical Queensland, Australia. Longitudinal changes in floodplain inundation were quantified using river gauge data, local stage recorders and HEC-RAS modelling based on LiDAR topographic data. Intra-and interannual gully scarp retreat rates were measured using daily time-lapse photographs and annual GPS surveys. Erosion was analysed in response to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 82 publications
2
62
0
Order By: Relevance
“…The first two methods were the focus for generating local knowledge from former and present day workers at Oriners Station, and the field visits and literature surveys were important in generating additional scientific information. Shellberg's previous hydro-geomorphic research (Shellberg et al 2010(Shellberg et al , 2013Shellberg 2011) about the lower Mitchell River catchment were augmented with additional scientific analyses of the Oriners Station landscape from local and regional datasets (Barber et al 2012). Formal scientific sampling of Oriners Station was not part of the research scope and was not undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…The first two methods were the focus for generating local knowledge from former and present day workers at Oriners Station, and the field visits and literature surveys were important in generating additional scientific information. Shellberg's previous hydro-geomorphic research (Shellberg et al 2010(Shellberg et al , 2013Shellberg 2011) about the lower Mitchell River catchment were augmented with additional scientific analyses of the Oriners Station landscape from local and regional datasets (Barber et al 2012). Formal scientific sampling of Oriners Station was not part of the research scope and was not undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…Brooks et al (2014aBrooks et al ( , 2014b and Caitcheon et al (2012) have questioned the significance of hill slope erosion in tropical catchments, suggesting bank erosion (Caitcheon et al, 2012) is more important. Similarly, Wasson et al (2002), Brooks et al (2009) and Shellberg et al (2013) have suggested that gully erosion is also a significant source of sediment. However, the contribution of floodplains as a sediment source, particularly when and if they experience substantial or complete stripping, has received little attention for catchments draining to the GBR lagoon.…”
Section: Introductionmentioning
confidence: 94%
“…Daily delineation of index scarp locations from oblique photographs demonstrated that the total scarp retreat was the cumulative sum of numerous and variable daily changes over each wet season, most often as discrete failures of overhanging soil blocks. Both direct rainfall and infiltration‐excess runoff dominated scarp retreat at WPGC2a, in contrast to groundwater seepage and pore water pressure (Shellberg et al ., ). Shallow overland flow from the low‐gradient vegetated floodplain above the scarp was relatively clear compared to the turbid water runoff following erosion on the scarp face, indicating that ungullied parts of the catchment are not major sources of sediment.…”
Section: Resultsmentioning
confidence: 97%
“…The gully study catchment (WPGC2a) is located in remote northern Queensland, Australia (–16°28'16" , 143°46'36" ; Shellberg et al ., ). WPGC2a is one alluvial gully of thousands delineated and described by Brooks et al .…”
Section: Methodsmentioning
confidence: 99%